2010
DOI: 10.4314/gmj.v40i3.55268
|View full text |Cite
|
Sign up to set email alerts
|

Human pulmonary infections with bovine and environment (atypical) Mycobacteria in Jos, Nigeria

Abstract: SUMMARYObjectives: To examine sputum specimens from patients with persistent bronchopulmonary disorders for mycobacterium species and to characterize the recovered isolates with a view to determining the extent of involvement of environmental mycobacteria in pulmonary infections. Design: Analytical study using standard microscopy, culture and biochemical test for the identification of mycobacterium species. Setting: Jos University Teaching Hospital (JUTH) and 2 referral hospitals: Plateau Specialist Hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 5 publications
1
30
5
1
Order By: Relevance
“…Cattle could have acquired the infection through contaminated environment during grazing or at water sources. The high prevalence of NTM seen in this study in both cattle and human is even lower than the previous reports in Jos, Nigeria by Mwak et al [29] who reported a prevalence of 23.08% in humans, and also in Tanzania by Shirima et al [30] and Durnez et al [31] reported prevalence of 6% and 10% respectively in cattle. Similarly, in their study Mdegella et al [32] and Durnez et al [31] found also high prevalence of 14% and 19% of NTM in milk samples.…”
Section: Discussioncontrasting
confidence: 75%
“…Cattle could have acquired the infection through contaminated environment during grazing or at water sources. The high prevalence of NTM seen in this study in both cattle and human is even lower than the previous reports in Jos, Nigeria by Mwak et al [29] who reported a prevalence of 23.08% in humans, and also in Tanzania by Shirima et al [30] and Durnez et al [31] reported prevalence of 6% and 10% respectively in cattle. Similarly, in their study Mdegella et al [32] and Durnez et al [31] found also high prevalence of 14% and 19% of NTM in milk samples.…”
Section: Discussioncontrasting
confidence: 75%
“…In Nigeria, the prevalence of pulmonary tuberculosis from M. bovis varies from 10% in the southern part of the country to about 15% in the more nomadic north (107). Similarly to most African communities, in Nigeria cow milk is often pooled and consumed without any form of pasteurization or purification (74).…”
Section: Rapid Identification Of Cultured M Tuberculosis Complex Isomentioning
confidence: 99%
“…In the light of this disease as a re-emerging zoonosis worldwide and particularly in developing countries like Nigeria, due to increasing incidences of HIV/AIDS infections Katibi, 2006, 2007), a thorough epidemiological assessment is required. Previous epidemiological studies on human tuberculosis in Nigeria were based on mycobacterial culture and they revealed approximately 3.9% of culture positive isolates were M. bovis (Idigbe et al, 1986;Mawak et al, 2006). Recently, MTC strains isolated from human samples in Nigeria were characterized using molecular methods like spoligotyping.…”
Section: Introductionmentioning
confidence: 99%